Solitary rectal ulcer syndrome – a potential diagnostic and management dilemma for the surgeon - S., Kumari; Talib, Arni; Gul, Yunus A. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Occult mucosal prolapse syndrome, also known as the solitary rectal ulcer syndrome (SRUS) is uncommon. Due to its rarity, a misdiagnosis of rectal cancer is occasionally made as the clinical features may closely mimic those of rectal malignancy. We hereby report a case of SRUS in an elderly Malay gentleman who had primary symptoms of rectal bleeding with associated anaemia and anorectal pain. Even though the clinical features and specific investigations suggested the presence of rectal cancer, preoperative histological analysis failed to confirm this. In view of the intractable symptoms and rectal bleeding, allow anterior resection was performed. A detailed examination of the resected specimen intraoperatively, together with the histological report and awareness of this condition avoided the performance of an abdominoperineal resection. Incidentally coexisting malrotation of the sigmoid colon to the right side was discovered during surgery. This finding, which may be coincidental, has not been reported thus far in the medical literature. The patient’s symptoms improved postoperatively with subsequent uneventful recovery. A brief literature review supplements this report.